(untitled) (Innovative professional education, 2024)
Features of the interaction between business and the system of vocational education based on the analysis of modern legislative, regulatory and legal documents, scientific sources and practical experience in the context of the needs of the post-war economic recovery of Ukraine are explicated. Cooperation projects between vocational education and business operating in the Ukrainian social space in the perspective of public-private partnership development at the current stage of interaction between public and private stakeholders interested in such interaction are characterized. Aspects of practical experience in public-private partnership’s development in Switzerland were analyzed through examples of interaction between business and vocational education system, as well as some recommendations concerning the application of the experience of cooperation between business’ and vocational education system’s stakeholders in Ukraine were offered. Results in the field of vocational education brand building, in particular, examples of several communication projects with well-known Ukrainian agencies and companies are given.